2008
DOI: 10.1111/j.1600-9657.2007.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial injuries sustained during soccer: incidence, severity and risk factors

Abstract: A very popular sport worldwide, soccer generates a great number of maxillofacial injuries, mainly fractures, resulting in esthetic or functional problems. The aim of this retrospective study was to contribute to the knowledge of soccer-related maxillofacial injuries, and call attention to the risk factors that favor these injuries. A total of 108 patients, who attended hospital because of maxillofacial injuries during soccer within a period of 8 years, were included in this study. The relationship of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 32 publications
5
30
1
Order By: Relevance
“…Greater speed and contact increase the risk of trauma. Soccer was found to be associated with high risks of facial and dental injuries (5,13,(15)(16)(17). However, previous studies enrolled professional soccer players and/or coaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater speed and contact increase the risk of trauma. Soccer was found to be associated with high risks of facial and dental injuries (5,13,(15)(16)(17). However, previous studies enrolled professional soccer players and/or coaches.…”
Section: Discussionmentioning
confidence: 99%
“…Soccer-related injuries represented 20.8% (11 of 53) of all oral and craniofacial injury cases at the Maxillofacial Surgery Department of Dentistry Faculty, Erzurum, Turkey. Another study, in Greece, reported that 103 of the 173 patients requiring treatment for trauma during an 8-year period were amateur soccer players (13). Lack of proper training and protection may explain this high prevalence among amateur athletes (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stricter regulations are needed to discourage violent play, rather than relying on the use of protective equipment 6,26 . Medical checkups could also contribute to the prevention of sports-related injury if they include the maxillofacial area, and sports coaches and sports physicians should be informed about maxillofacial injuries 25,26 . More studies are needed to investigate the effects of changes in rules and safety standards to provide beneficial information for the prevention of maxillofacial injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This result in line with Papakosta et al (17) which reported that 103 of the 173 patients requiring restoration treatment for trauma during an 8-year period were amateur soccer players and these findings is disagreement with Paulo et al, 2014 that reported the high percent of extractions type -51% that need treatment. This study is the first study to represented information about dental treatment need among footballers therefore, on previous data to compare with finding of the study.…”
Section: Resultsmentioning
confidence: 51%